Motivations to conduct research and burnout in medical education: A mixed methods study of students and residents - Box, Devin; Healey, Skylar; Mihilli, Stefani; Barton, Kristen; Degen, Ryan; Ott, Mary (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Background: Burnout is on the rise in medical training as workload increases. One such demand is the pressure for research productivity earlier in training. However, little is known about the impacts of this trend and its mediating factors as trainees progress. Important influences may be motivation sources and supports, since intrinsic motivation is linked to well-being. This mixed methods study investigated associations between burnout and motivations for conducting research in a sample of medical students and residents in one academic centre.Methods: Participants completed an online survey including validated scales for measuring burnout (Maslach Burnout Inventory) and intrinsic research motivation (using the Situational Motivation Scale) along with open response items to identify supports for autonomy, competence, and relatedness in the process of conducting research. Results were synthesized from the statistical and thematic analyses, using the framework of self-determination theory.Results: Forty-three survey responses were analyzed. Overall prevalence of burnout was high (60.5%) and evidenced a progressive impact, with a significant increase in depersonalization among residents compared to medical students. Participants articulating more intrinsic reasons for doing research had lower levels of burnout. Intrinsically motivated individuals were more likely to have increased relational and academic supports and less likely to internalize barriers to conducting research. Residents expressed more competence in their ability to do research but less relational supports.Discussion/Conclusions: Burnout is a multifaceted condition requiring multiple mitigation strategies. This study identified a correlation between research motivation and burnout and mediating protective factors. These findings can inform study of interventions focussed on targeted motivational supports to advance research training in medical education.